HIV Screening and the Affordable Care Act. (March 2017) - Carter, Greg; Owens, Christopher; Lin, Hsien-Chang
Men continue to bear disproportionate accounts of HIV diagnoses. The Patient Protection and Affordable Care act aims to address health care disparities by recommending preventative services, including HIV screening, expanding community health centers, and increasing the healthcare workforce. This study examined the decision making of physician and primary care health providers to provide HIV screenings. A quasi-experimental design was used to estimate the effects of the Affordable Care Act on provider-initiated HIV screening. The National Ambulatory Medical Care Survey was used to examine HIV screening characteristic from two time periods: 2009 and 2012. Logistic regression indicated that patient and provider characteristics were associated with likelihood of being prescribed HIV screening. Non-Hispanic Black men were more likely to be prescribed HIV screening compared to non-Hispanic White men (odds ratio [OR] = 12.33, 95% confidence interval [CI; 4.42, 34.46]). Men who see primary care providers were more likely to be prescribed HIV screening compared to men not seeing a primary care provider (OR = 5.94, 95% CI [2.15, 16.39]). Men between the ages of 19 and 22 were more likely to be prescribed HIV screening compared to men between the ages of 15 and 18 (OR = 6.59, 95% CI [2.16, 20.14]). Men between the ages of 23 and 25 were more likely to be prescribed HIV screening compared with men between the ages of 15 and 18 (OR = 10.13, 95% CI [3.34, 30.69]). Health education programs identifying men at increased risk for contracting HIV may account for the increased screening rates in certain populations. Future research should examine age disparities surrounding adolescent and young men HIV screening.